TEACHERS OF COMMUNICATION MANAGEMENT PERFORMANCE - Nurhalimah Harahap (Universitas Islam Negeri (UIN) Sumatera Utara, 2020)
The results of this study revealed three findings: first, the implementation of the communication head of Madrasah with teachers in the performance improvement teachers in Madrasah Tsanawiyah Al-Jam'iyatul Washliyah Tembung performed continuously and scheduled. Secondly, the implementation of teacher communication with the head of Madrasah in improving the teacher's performance in Madrasyah Tsanawiyah Al-Jam'iyatul Washliyah Tembung is continuing to establish communication of working relationship both information and communication assignments and also by the head of the Madrasah to the teacher. Thirdly, the implementation of communication between fellow teachers, education personnel in improving the performance of teachers in Madrasah Tsanawiyah Al-Jam'iyatul Washliyah Tembung is exchanging information about both the task information and information that develops or and brainstorm both fellow teachers and fellow educations.